2000
DOI: 10.1073/pnas.150242097
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental patterns underlying gene expression profiles: Simplicity from complexity

Abstract: Analysis of previously published sets of DNA microarray gene expression data by singular value decomposition has uncovered underlying patterns or ''characteristic modes'' in their temporal profiles. These patterns contribute unequally to the structure of the expression profiles. Moreover, the essential features of a given set of expression profiles are captured using just a small number of characteristic modes. This leads to the striking conclusion that the transcriptional response of a genome is orchestrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
255
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(262 citation statements)
references
References 9 publications
4
255
0
1
Order By: Relevance
“…After between-slide normalization was done with the cluster program, 13 we performed a principal-components analysis (PCA). 14 The PCA identifies a set of statistically independent components of gene expression. The first 2 components that captured the 2 greatest fractions of the overall variance of the samples were plotted against each other.…”
Section: Microarray Data Analysismentioning
confidence: 99%
“…After between-slide normalization was done with the cluster program, 13 we performed a principal-components analysis (PCA). 14 The PCA identifies a set of statistically independent components of gene expression. The first 2 components that captured the 2 greatest fractions of the overall variance of the samples were plotted against each other.…”
Section: Microarray Data Analysismentioning
confidence: 99%
“…Molecular inhibitors of intracellular calcium, cAMP and AP-1, were used to identify possible upstream signaling pathways involved in the mechanotransduction of the genes studied here. Clustering analysis (27,28) and principal component analysis (29,30) were used to elucidate the main expression trends and to highlight genes that appeared to be co-regulated by mechanical compression. These computational techniques can help to classify groups of genes with common upstream signaling pathways and may help to predict certain cell behavior (28,30).…”
mentioning
confidence: 99%
“…Clustering analysis (27,28) and principal component analysis (29,30) were used to elucidate the main expression trends and to highlight genes that appeared to be co-regulated by mechanical compression. These computational techniques can help to classify groups of genes with common upstream signaling pathways and may help to predict certain cell behavior (28,30). We found that both anabolic and catabolic genes were induced by static compression, but with contrasting expression patterns.…”
mentioning
confidence: 99%
“…Quantitative simulation of these time dependent gene expression patterns meets with difficulties due to incomplete knowledge of the underlying regulatory mechanisms. However, statistical methods have been successfully applied, such as cluster analysis of time-dependent gene expression patterns for identifying functionally related proteins [5][6][7][8][9][10].It has been stressed that even without detailed knowledge of gene regulatory mechanisms phenotype properties can be rationalized by evolutionary optimization principles [11]. The basis of this approach is the hypothesis that a permanent change of phenotype properties due to mutation and selection leads to an optimal adaptation of an organism to given environmental conditions.…”
mentioning
confidence: 99%
“…Quantitative simulation of these time dependent gene expression patterns meets with difficulties due to incomplete knowledge of the underlying regulatory mechanisms. However, statistical methods have been successfully applied, such as cluster analysis of time-dependent gene expression patterns for identifying functionally related proteins [5][6][7][8][9][10].…”
mentioning
confidence: 99%